Remarkable photocatalytic performance of zinc oxide nanoparticles prepared through green synthetic method by using Citrus limon dry peel extract - Waiba, Sushan; Sharma, Motee Lal; Sapkota, Kamal Prasad (Scientific World, 2024)
Zinc oxide nanoparticles (ZnO NPs) were synthesized through green synthetic method using Citrus limon (Lemon) dry peel extract which acts as a reducing agent. The synthesized nanoparticles were yellowish white and their UV-vis spectra showed the characteristic maximum peak at 332 nm which affirmed the formation of zinc oxide nanoparticles. For further confirmation, the synthesized nanoparticles were characterized through X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Field Emission Scanning Electron Microscopy (FE-SEM) and High-Resolution Transmission Electron Microscopy (HR-TEM). The most intense peak in the XRD pattern was selected for crystallite size determination by using the Scherrer’s equation; the average crystallite size was computed to be 19 nm. FE-SEM results demonstrated the spherical shape of nanoparticles with less distinct morphology. The hexagonal structure of ZnO NPs was identified by HR-TEM. ZnO NPs showed excellent catalytic activity of 50.25% photodegradation of MB under natural sunlight irradiation for 120 minutes. The results show that the as-synthesized ZnO NPs can have possible application in water treatment for removing harmful dyes. The phytochemical screening of dry Citrus limon peel extract revealed the presence of alkaloids, flavonoids, cardiac glycosides, saponins, terpenoids, tannins, and reducing sugar.